HIEROFANIE EROTYCZNE W OBRZĘDOWOŚCI RZYMSKIEJ - Kaczor, Idaliana (Collectanea Philologica, 2013)
The article presents erotic behaviours by the participants of some sacral ceremonies of ancientRome. These celebrations belong to the group of sacra publica (sacrum Annae Perennae,Parilia, Floralia, Veneralia, the festival in honour of Juno with the epithet Sororia), as well as ofsacra privata (the marriage rites connected to the god Mutunus Tutunus). The basic aim of sacralrites with intensive sexual features was to increase the biological forces cumulated in earth andplants which, through magical references, increase the organic forces in other animated elementsof the cosmos, i.e. animals and humans. According to a sacral society, such socially acceptedbehaviour was voluntary and efficient, it reflected the primary idea of religious celebrations,assisted the activity of divine powers, allowed people to participate in the activities of the numenand co-create the scenario of the festival.